What makes a giant fruit? Assembling a genomic toolkit underlying various fruit traits of the mammoth group of Cucurbita maxima - Reddy, Umesh K.; Natarajan, Purushothaman; Abburi, Venkata Lakshmi; Tomason, Yan; Levi, Amnon; Nimmakayala, Padma (Frontiers in Genetics, 2022)
Since their introduction in Europe, pumpkins (Cucurbita maxima Duch.) have rapidly dispersed throughout the world. This is mainly because of their wide genetic diversity and Plasticity to thrive in a wide range of geographical regions across the world, their high nutritional value and suitability to integrate with local cuisines, and their long shelf life. Competition for growing the showy type or mammoth-sized pumpkins that produce the largest fruit of the entire plant kingdom has drawn attention. In this study, we used genome-wide single nucleotide polymorphisms to resolve admixture among different pumpkin groups. Also, to resolve population differentiation, genome-wide divergence and evolutionary forces underlying the evolution of mammoth-sized pumpkin. The admixture analysis indicates that the mammoth group (also called Display or Giant) evolved from the hubbard group with genome-wide introgressions from the buttercup group. We archived a set of private alleles underlying fruit development in mammoth group, and resolved haplotype level divergence involved in the evolutionary mechanisms. Our genome-wide association study identified three major allelic effects underlying various fruit-size genes in this study. For fruit weight, a missense variant in the homeobox-leucine zipper protein ATHB-20-like (S04_18528409) was significantly associated (false discovery rate = 0.000004) with fruit weight, while high allelic effect was consistent across the 3 years of the study. A cofactor (S08_217549) on chromosome 8 is strongly associated with fruit length, having superior allelic effect across the 3 years of this study. A missense variant (S10_4639871) on translocation protein SEC62 is a cofactor for fruit diameter. Several known molecular mechanisms are likely controlling giant fruit size, including endoreduplication, hormonal regulation, CLV-WUS signaling pathway, MADS-box family, and ubiquitin-proteasome pathway. This study provides a general framework for the evolutionary relationship among horticulture groups of C. maxima and elucidates the origins of rare variants contributing to the giant pumpkin fruit size.